HUBUNGAN PENGETAHUAN DAN SIKAPREMAJA TENTANG KESEHATAN REPRODUKSI DENGAN PERILAKUSEKSUAL DI SMABAYU PERTIWI SUNGGAL TAHUN 2015 - desy ramayanty; Sri Rahayu Sanusi; Maya Fitria (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT According to National Family Planning Coordination Board obtained that 51 % teenagers in Jakarta, Bogor, Tangerang, Depok, Bekasi (JABODETABEK) have performed intercourse before marriage. The same problem is also happened other cities in indonesia such as 54% in Surabaya, 47% in Bandung, 52% in Medan. The research aims to know the correlation of knowledge and attitude in reproduction health on teenagers with sexual behaviour at Bayu Pertiwi High School in Sunggal in year 2014. This research is an analytic descriptive using Cross Sectional Study approach. The population in this research were all students of Bayu Pertiwi High School from grade X, XI, XII, and the number of responden were 114 students. Giving questionaire was the methode to collect some data, and then conducting statistic experiment using Chi-Square test with level of significance Alpha = 0,05 From bivariate analysis was obtained the results that knowledge of reproduction health correlates sexual behaviour on teenagers with p value= 0,001 and attitude on sexual behaviour on teenagers with p value= 0,007 and from the variable of knowledge and intercourse attitude with sexual behaviour on teenagers, it is very important to improve their knowledge about reproduction health and intercourse.